The essential elements of undergraduate medical education in obstetrics and gynecology: A comparison of the Association of Professors of Gynecology and Obstetrics Medical Student Educational Objectives and the National Board of Medical Examiners Subject Examination - Hammoud, Maya M.; Cox, Susan M.; Goff, Barbara; Goepfert, Alice; Butler, Aggie; Swanson, David B.; Holtzman, Kathleen Z.; Allbee, Krista; Katz, Nadine T.; Erickson, Sonya S. (American journal of obstetrics and gynecology, 2005)
The objective of this study was to investigate whether the essential elements of the Association of Professors of Gynecology and Obstetrics (APGO) Medical Student Educational Objectives were adequately represented on the National Board of Medical Examiners (NBME) obstetrics and gynecology subject examination, and that the topics questioned on that examination were covered by the APGO objectives. The Undergraduate Medical Education Committee of APGO and the NBME staff separately reviewed the same 2 NBME obstetrics and gynecology subject examinations. The questions were mapped to the 15 essential elements of the APGO educational objectives and comparisons were made to check how well they matched. All the essential elements of the educational objectives were covered by the NBME subject examination. Of the questions on the examination, 99% were deemed appropriate for medical students with 70% of the questions mapping to “Priority 1” objectives. The NBME examination provides an appropriate assessment of mastery of what a medical student should learn, as represented by the APGO Medical Student Educational Objectives.